Analisis Hermeneutika Ayat-Ayat Mutasyabihat: Pendekatan Kaidah Al-Isti’arah Dan Al-Tasybih Dalam Ushul Tafsir - Helga Juliya; Intan Anggrini; Akhmad Dasuki (CV. KAMPUS AKADEMIK PUBLISING, 2025)
. This research investigates mutashabihat verses in the Qur'an through the lens of hermeneutics, focusing on applying the principles of al-isti'arah (metaphor) and al-tashbih (simile) as stipulated within the discipline of ushul tafsir. Mutashabihat verses, characterized by semantic ambiguity and a plurality of interpretations, frequently spark discourse among exegetes. Adopting a hermeneutical approach facilitates the deconstruction of intrinsic meanings by considering linguistic, historical, and theological contexts. The principles of al-isti'arah and al-tashbih, as rhetorical instruments of the Qur'an, are essential in the effective transmission of divine messages. This study aims to identify the modus operandi of implementing these two principles in the explication of mutashabihat verses and their contribution to holistic comprehension. The research findings are expected to contribute substantially to the methodology of Qur'anic exegesis, particularly in addressing textual ambiguity, and to enrich the scholarly corpus of ushul tafsir.